Governing Stunting through Power, Discourse, and Local Resistance in Indonesia - Shobirin Noer; Kasanusi; Endah Wahyuningsih (Universitas Darul Ulum, 2026)
The issue of stunting has largely been treated as a biomedical problem to be solved through technical intervention without considering the politics of the problem. This paper seeks to analyze how the governance of stunting occurs within the power/knowledge complex and how communities interact with such interventions in the Indonesian case. In a qualitative study carried out using case study methodology within Ngusikan village, data was gathered using interview, focus group discussion, observation and documentation methods involving twenty-two respondents. Using the Foucault-inspired theoretical perspective, the study identifies three key dynamics of how stunting governance happens: (1) the processes of governance involve surveillance and normalization through the posyandu and growth monitoring systems; (2) medical discourse represents the dominant regime of truth, which continually competes with the local knowledge; and (3) communities, especially mothers, creatively respond to such interventions.